Type B Aortic Dissection Diagnosed by Left-Sided Transthoracic Ultrasonography in a Woman With Preeclampsia. Issue 6 (15th September 2018) - Winiszewski, Hadrien; Pili-Floury, Sebastien; Capellier, Gilles; Piton, Gaël; Besch, Guillaume
Abstract : Supplemental Digital Content is available in the text.